Peran Persepsi Pemberdayaan Terhadap Diabetes Distress pada Pasien Diabetes Tipe 2 - inayati, aini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: The purpose of this study was to examine the relationship between the role of empowerment and diabetes distress in patients with type 2 diabetes in Indonesia. Methods: A cross-sectional design was used in this study. A total of 162 adult patients with type 2 diabetes were recruited from two health centers using convenience sampling. Self-report questionnaires and medical records were used to collect data on demographic and disease characteristics, the role of empowerment and diabetes distress. Bivariate analysis was used to test for significant correlations of variables.Results: The results of this study were that the role of perceived empowerment was negatively associated with diabetes distressConclusion: The importance of empowerment decision-making conflicts with diabetes distress in patients with type 2 diabetes in Indonesia. Health care providers need to be aware that increasing the perception of empowerment without considering decision-making conflict can increase diabetes distress.